Por um devir ecosófico: uma investigação a partir de Guattari e Deleuze - Padilha, Alan Rodrigo (2025)
This research delves into the concept of ecosophy and ecosophical becoming, referencing the conception of an ecology of thought as articulated by Guattari and Deleuze. The study aims to explore the concept of ecosophy, framing it as a transversal approach that integrates ethical-aesthetic and political dimensions while challenging the paradigms established by the tradition of Western thought. The thesis posits the hypothesis that the concept of ecosophy expresses an ecology of thought. In this regard, the guiding question of the research is: "How can the articulation between the practical and speculative objects of the concept of ecosophy be conceived to justify the ecosophical becoming that traverses Anti-Oedipus and A Thousand Plateaus, unfolding into contemporary ecosophical becomings?"To address this question, the thesis is structured into three chapters. The first chapter explores the general conceptions of ecosophy, emphasizing its connections and distinctions concerning political ecology and eco-philosophy. This initial analysis positions ecosophy as a transversal approach that integrates ethical-aesthetic and political dimensions while critiquing the capitalist logic of production and sustainable consumption. It highlights the limits and contradictions of the dominant sustainability discourse, particularly within the contexts of the Club of Rome and the United Nations Conference on Environment and Sustainable Development. The second chapter expands on the understanding of ecosophical thought as an expression of an ecology of thought operating through a process of conceptual becoming. It begins with a critique of classical naturalism, which perpetuated the separation between nature and thought, to explore the conception of geophilosophy and the rhizome. These constitute what may be called a "strange ecology," dissolving distinctions between the natural and the artificial, nature and thought, and rejecting the separation between nature and industry. Everything is conceived as part of a disjunctive synthesis of heterogeneities, involving rhizomes that connect the animal, vegetal, mineral, and machinic realms. The third chapter examines the idea of machinic ecology, processes of subjectivation, desiring-machines, linguistic and semiotic machines, and collective assemblages of desire. It also considers the practical object of ecosophy, aiming to produce subjectivities engaged in reinventing ways of being, in constant re-singularization against the modeling serialization of the system of capitalist subjectivation and subjugation. Additionally, it explores a new conception of subjectivation processes, considering them not only intersubjective but also machinic and cosmic. Ecosophical becoming is guided by a practice that values creative dissent and fosters new modes of relating to the socius, alterity, the environment, and the psyche. The research demonstrates that, far from being confined to the traditional paradigms of political and economic ecology, ecosophical thought constitutes a revolutionary collective assemblage capable of addressing the complex challenges of the contemporary world. In opposition to anthropo-capitalocentric logic, it proposes innovative practices, such as "composting" and "white magic," which challenge and subvert the predatory dynamics of global capitalism, pointing towards sustainable and transformative alternatives.